Synthesis of 3, 6-diaryl-1H-pyrazolo[3, 4-b]pyridines via one-pot sequential Suzuki–Miyaura coupling. Issue 61 (11th October 2018) - Urvashi; Tandon, Vibha; Das, Parthasarathi; Kukreti, S.
Abstract : An efficient method to produce diarylpyrazolo[3, 4- b ]pyridines derivatives via combination of chemoselective Suzuki–Miyaura cross-coupling reactions has been developed. Abstract : A practical synthesis of diarylpyrazolo[3, 4- b ]pyridine derivatives by a combination of chemoselective Suzuki–Miyaura cross-coupling reactions was developed. The sequential arylation strategy can be performed in a one-pot manner without much loss of efficiency when compared to the corresponding stepwise synthesis. These conditions are applicable to the coupling of a wide variety of aryl and heteroaryl-boronic acids with pyrazolo[3, 4- b ]pyridines with high selectivity of the C3 over the C6 position, thus enabling the rapid construction of a diverse array of medicinally important diarylpyrazolo[3, 4- b ]pyridines.